Mumi Fir’aun dalam al-Qur’an: Studi QS. Yunus [10]:92 Perspektif Tafsir Al-Mishbah - Raisa Zuhra Salsabila Awaluddin; Lukmanul Hakim (Universitas Darussalam Gontor, 2023)
This study allude to the story of the discovery of the Pharaoh's mummy as informed in the Qur'an. The discovery of Pharaoh's mummy can be investigated in modern discoveries or research, as was done by Maurice Buceille who found traces of salt in Pharaoh's mummy. Before research on Pharaoh's mummies, archaeologist Loret made the initial finding of this mummy. Elliot Smith then carried out research and discovered Pharaoh's body, which was still intact. Pharaoh indeed perished in the sea. This work poses the topic of how to interpret Quraish Shihab's view of the Qur'anic tale and how to explain it. Yunus [10]: 92, How accurate is Maurice Buceille's account of finding a mummy of a Pharaoh and converting to Islam as a result? This paper examines library research, using qualitative methods. The goal of this study is to highlight the opinions of Quraish Shihab in Al-interpretation Mishbah as an Indonesian interpreter who provides in-depth explanations of the pharaoh's mummy that were discovered after centuries. As well as explaining the inspiring story that converted to Islam after his research on the mummy of the Pharaoh named Maurice Bucaille which is also presented in Tafsir Al-Mishbah